An Autopsy based unaided Eye Study of Lambdoid Suture of Skull– the Science of Forensic Estimation of Age - Zulfiqar Ali Buzdar, Mubarak Mehmood Ahmad Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The criminal investigation starts at crime scene and ends in the laboratory. The most vital of which is mortuary where the postmortem examination of the deceased is carried out to answer the questions of interest in that investigatory menu. Aim: Unaided eye estimation of age from the lambdoid suture of skull on autopsy. Methods: The subjects under study were taken from mortuary of the department of Forensic Medicine and Toxicology in the King Edward Medical University Lahore during the year 2016. The targeted population for study was the draining are of the mortuary of King Edward Medical College having designated police station. A pretested questionnaire was used to collect the calculated sample among the research population as a research method. A non-probability convenient consecutive sampling technique was applied to collect the data. The comparative descriptive study design was utilized to analyze the results. Results: The study revealed that among the targeted population a higher percentage more than third of the sample size were adolescents of age between 21 – 30 years being 35% followed by elderlies of age between 41 – 50 years amount to 20%. The research depicted that age can be determined from degree of closure of lambdoid suture in the dead body on the autopsy table with closure taking place earlier in males as compared to that of females. Conclusion: This study concludes that it is possible to estimate age from the degree of lambdoid suture closure of the deceased skull vault during the postmortem examination. Keywords: Age, Lambdoid, Suture, Autopsy, Cranial, Post-mortem Examination, Skull